Pharmacognostical and Phytochemical Studies on Stem Bark of Ailanthus Excelsa Roxb. (Simaroubaceae) - G. PRAKASH YOGANANDAM; K.PERIYANAYAGAM; K.ILANGO (International Journal of Pharma and Bio Sciences, 2010)
Ailanthus excelsa, Roxb (Family-Simaroubaceae) is a large deciduous tree, 60-80 inch in height and 6-8 inch in girth with rough and light grey bark. It has a large panel of indication and it would be more suitable to evaluate the bark since it has been used in diarrhoea, dysentery, cholera, astringent, febrifuge, anthelmintic and liver tonic. The present paper highlights the exomorphology, histomorphology, physicochemical evaluation and preliminary phytochemical studies of the bark. For the better understanding of structural details Scanning Electron Microscopy (SEM) also employed. These observation will enable to standardize the botanical identify of the drug in its crude form. Data evolved in this investigation could be used in laying down pharmacopoeial standards for the drug studied, as standardization of herbal medicines is absolutely essential and is need of the hour.